Horizons : the Tata - India century 1904-2004 / by Aman Nath and Jay Vithalani - "Nath, Aman" (Bombai, 2004)
- Founded in the late 19th century by the great industrialist and philanthropist Jamsetji Tata, the Tata Group has been a pioneer in such nationally vital industries as steel, hydroelectricity, aviation, and information technology; the history of the Group is in significant measure the history of India's industrial development. Horizons: The Tata-India Century, 1904-2004 commemorates the death centenary of Jamsetji Tata and the birth centenaries of two men who helped guide the Group's destiny: JRD Tata and Naval Tata. Illustrated with rare archival images as well as spectacular contemporary photographs, the book interweaves the Tata story directly with the history of modern India, allowing the reader to make connections between two parallel narratives.
Keywords: Tata group of companies-India-1904-2004